Creating Visual Work Instructions to Ensure Safe and Fluent Operation of the Semi-automatic Production Lines - Beluško Matúš; Hegedüš Matúš; Fedorko Gabriel (Open Engineering, 2016)
The process of robotics in the world, but also in Slovakia is constantly increasing, and although new types of robots are being developed, the human hand of those work stations cannot be removed completely. Despite the already developed and functioning collaborative robots that allow safe operations side by side with humans, it is necessary for a worker to known accurate, fast and safe procedure of his working activities. Visual work instructions (VWI) are made for this purpose. The worker must be able to quickly understand the principle of work procedure and get quick information about potential risks in very short time. Therefore, great regard for the content of VWI must be taken. At first glance, a simple visual work instructions enable not only to increase safety at the workplace, but also increase workers productivity.